Issues in Extractive Resource Taxation : A Review of Research Methods and Models - Smith, James (IMF Working Papers; Working Paper ;, 2012)
This paper provides a conceptual overview of economists' attempts to learn about the effects of taxes on extractive resources. The emphasis is on research methods and techniques, with no attempt to provide a comprehensive tabulation of previous empirical results or policy conclusions regarding preferred tax instruments or systems. We argue, in fact, that the nature of such conclusions largely depends on the researcher's choice of modeling framework. Many alternative frameworks and approaches have been developed in the literature. Our goal is to describe the differences among them and to note their strengths and limitations.